Effects of Telmisartan on Right Ventricular Remodeling Induced by Monocrotaline in Rats - Muneyoshi Okada; Toshiyuki Harada; Ryuta Kikuzuki; Hideyuki Yamawaki; Yukio Hara (Elsevier, 2009)
The present study investigated whether telmisartan, an angiotensin II type 1 receptor antagonist, has cardioprotective effects on monocrotaline-induced right ventricular (RV) remodeling in rats. Six-week-old male Wistar rats were divided into control group (CONT), monocrotaline (60 mg/kg, i.p.)-treated group (MCT), monocrotaline (60 mg/kg, i.p.) + telmisartan (3 mg/kg per day, p.o.)-treated group (MCT+TEL), and telmisartan (3 mg/kg per day, p.o.) alone- treated group (TEL). Hearts were excised after echocardiography examinations at day 25. Significant increase in RV weight and histologically remarkable fibrosis in RV sections were observed in MCT. Tricuspid annular plane systolic excursion, a parameter for RV systolic function, significantly decreased in MCT. These RV hypertrophy, fibrosis, and dysfunction were inhibited in MCT+TEL. In MCT, the acceleration time/ejection time ratio of pulmonary artery flow velocity, an index of pulmonary hypertension, significantly decreased. This decrease was not affected in MCT+TEL. In MCT, expressions and activities of matrix metalloproteinase (MMP)-2 and MMP-9, which play a critical role in cardiac remodeling, significantly increased in the RV. In MCT+TEL, these increases in expressions and activities were inhibited. MCT showed about 2-fold increase in transforming growth factor-β 1 expression compared with CONT, and such an increase was not decreased in MCT+TEL. There were no significant changes of these parameters in TEL compared with CONT. These results suggest that telmisartan could attenuate the monocrotaline-induced RV remodeling through improvements of RV hypertrophy, fibrosis, dysfunction, and inhibition of MMPs. Keywords:: angiotensin II type 1 receptor, matrix metalloproteinase, monocrotaline, right ventricular remodeling, telmisartan